Epigenetic suppression of E-cadherin expression by Snail2 during the metastasis of colorectal cancer - Yue Hu (Clinical Epigenetics, 2018)
Abstract Background The transcription factor Snail2 is a repressor of E-cadherin expression during carcinogenesis; however, the specific mechanisms involved in this process in human colorectal cancer (CRC) remain largely unknown. Method We checked the expression of Snail2 in several clinical CRC specimens. Then, we established Snail2-overexpressing and knockdown cell lines to determine the function of Snail2 during EMT and metastasis processes in CRC. In addition, we used luciferase reporter assay to explore how Snail2 inhibits the expression of E-cadherin and induces EMT. Results We found that the expression of Snail2 was higher in clinical specimens of colorectal cancer (CRC) compared to non-cancerous tissues. Overexpression of Snail2 induced migration and metastatic properties in CRC cells in vitro and in vivo. Furthermore, overexpression of Snail2 promoted the occurrence of the epithelial–mesenchymal transition (EMT), downregulating the expression of E-cadherin and upregulating that of vimentin. Specifically, Snail2 could interact with HDAC6 and then recruited HDAC6 and PRC2 to the promoter of E-cadherin and thus inhibited the expression of E-cadherin, promoting EMT and inducing invasion and metastasis of CRC. Conclusion Our study reveals that Snail2 might epigenetically suppress the expression of E-cadherin during CRC metastasis.